1999
DOI: 10.1103/physrevb.60.14617
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carrier concentration on the superfluid density of high-Tccuprates

Abstract: The absolute values and temperature, T, dependence of the in-plane magnetic penetration depth, λ ab , of La2−xSrxCuO4 and HgBa2CuO 4+δ have been measured as a function of carrier concentration. We find that the superfluid density, ρs, changes substantially and systematically with doping. The values of ρs(0) are closely linked to the available low energy spectral weight as determined by the electronic entropy just above Tc and the initial slope of ρs(T )/ρs(0) increases rapidly with carrier concentration. The r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

26
131
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(158 citation statements)
references
References 34 publications
(40 reference statements)
26
131
1
Order By: Relevance
“…7 the normalized superfluid density ρ s (T )/ρ s (0) as a function of T /T c at various doping. In the overdoped regime, where the pseudogap closes, we recover the standard d-wave mean field result, which seems in a good agreement with experimental data [16] (see the curve for δ = 0.22 in Fig. 7).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…7 the normalized superfluid density ρ s (T )/ρ s (0) as a function of T /T c at various doping. In the overdoped regime, where the pseudogap closes, we recover the standard d-wave mean field result, which seems in a good agreement with experimental data [16] (see the curve for δ = 0.22 in Fig. 7).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Debye-Scherrer x-ray scans showed that approximately 90% of the grains had their CuO 2 planes aligned to within approximately 2°. The values of ab (0) Ϫ2 for samples with pу0.15 were also confirmed by standard TF SR experiments performed on unaligned powders at 400 G. 12,13 Figure 1 shows the typical time dependence at several temperatures of the ZF muon asymmetry [20][21][22][23] 01. In all samples the high-temperature form of the depolarization is Gaussian and temperature independent, consistent with dipolar interactions between the muons and their near-neighbor nuclear moments.…”
mentioning
confidence: 59%
“…19, just beyond optimal doping, 10,11 a behavior rather analogous to the quantum-critical heavy-fermion materials. 9 Many fundamental physical quantities such as the superconducting condensation energy, 10,11 the superfluid density, 12,13 and the quasiparticle weight, 10,14 show abrupt changes as p→p c . While compelling in their totality, 10,11 none of the results can be considered as evidence of a quantum transition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(We do not consider the wider class of materials discussed by Uemura [2]). To set the scene we show in field muon spin relaxation (µSR) studies [9] while the La-214 data are from ac susceptibility and µSR studies [10]. ρ s (0) data for Bi 2 Sr 2 CaCu 2 O 8+δ (Bi-2212) were obtained from fielddependent thermodynamic measurements [11].…”
mentioning
confidence: 99%